A question of ethics: the challenges for journalism practice as a mode of research. Issue 2 (1st September 2016) - Vine, Josie; Batty, Craig; Muir, Rilke
ABSTRACT: As journalism programmes continue to grow, journalism research – especially that which is practice-based – is declining. In Australia this is recognised by fewer universities submitting research outputs to the 'Journalism and Professional Writing' Field of Research Code, and in the latest Excellence in Research for Australia evaluation, no university scoring above 3 ('at world standard') out of 5 ('well above world standard'). For journalists transitioning from industry to academy, it is becoming an issue that their professional successes are largely unable to be translated into legitimate and important research identities. One core issue underpinning the arrested growth of journalism practice research is the approach to preparing and assessing ethics applications. Often perceived at odds with professional and personal codes of ethics, university processes informed by the National Statement in Australia, and other guidelines internationally, deter practitioner-researchers from undertaking quality journalism. In this paper we discuss the challenges of undertaking journalism as a mode of research, suggesting it is entirely feasible to take advantage of the in-built flexibilities of the National Statement. By doing this, not only can journalist-researchers build distinctive research identities, but also institutions can take advantage of the core fabric of journalism to generate research with cultural, social and political impact.